Sound sources of high directivity - WYRZYKOWSKI, R. (Archives of Acoustics, 1992)
The reversibility of Hankel transform suggests the possibility of constructing such a sound source which radiates only within a certain cone. Both the approximate and accurate theories of that source are given. It is proved in the paper that the accurate source is better than the aaproximate one. The source is called the source of high directivity.